Adiponectin Receptors and Pro-inflammatory Cytokines Are Modulated in Common Variable Immunodeficiency Patients: Correlation With Ig Replacement Therapy - Polito, Rita; Nigro, Ersilia; Pecoraro, Antonio; Monaco, Maria Ludovica; Perna, Franco; Sanduzzi, Alessandro; Genovese, Arturo; Spadaro, Giuseppe; Daniele, Aurora (Frontiers in Immunology, 2019)
Adiponectin, the most abundant and specific adipose tissue-derived cytokine, exerts protective effects and modulates inflammatory responses through its receptors, AdipoR1, AdipoR2, T-cadherin. Recently, emerging evidence suggests that adiponectin possesses immunomodulatory effects on immune cells. Previously, we demonstrated a deep involvement of adiponectin in Common Variable Immunodeficiency (CVID). The aim of the present study was to characterize the expression profile of AdipoRs on peripheral blood mononuclear cells (PBMC) as well as the potential involvement of other cytokines in CVID. AdipoR1, AdipoR2 and T-cadherin expression was detected by flow cytometry on PBMC from 18 naïve CVID patients (before and after the first Ig replacement therapy) in comparison to healthy controls. In addition, we measured the expression of adiponectin, leptin, IL-2, IL-6, IL-10, TNF and IFN in 24 maintenance therapy, 18 naïve CVID patients (before and after the first Ig replacement therapy) and in 28 controls. We found that: a) adiponectin is down-regulated in both maintenance therapy patients and naïve patients and that is strongly increased in naïve patients 24 hours after the first Ig infusion; b) Leptin is not different between maintenance patients and controls neither before nor after the first Ig infusion in naïve patients; c) B Lymphocytes, monocytes and NK cells from CVID patients have statistically higher expression of AdipoR1 vs controls; d) The expression of AdipoR1 and AdipoR2 on B Lymphocytes, monocytes and NK cells is modified after the first Ig infusion being increased; e) T-cadherin is not differentially expressed in naïve CVID patients vs controls and not modified by the first Ig infusion; f) IL-6, IL-8, IL-10, TNF levels are differently modulated in therapy maintenance CVID patients vs controls. This is the first study demonstrating that AdipoRs are differentially expressed on PBMC from CVID patients in comparison to controls and modified by the first Ig infusion. Furthermore, adiponectin is the only cytokine modulated by the first Ig infusion. Altogether these results suggest a specific role for the adiponectin system in CVID. A deeper knowledge on adiponectin as a link in the cross-talk between immune system and adipose tissue may provide additional benefits for the management of CVID patients.